2023
DOI: 10.1002/lio2.1017
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric indications for tonsillectomy and adenotonsillectomy: Race/ethnicity, age, and gender

Abstract: Objective To evaluate how pediatric indications for tonsillectomy or adenotonsillectomy relate to gender, race/ethnicity, and age. Methods Included consecutive pediatric patients who underwent tonsillectomy or adenotonsillectomy from a single tertiary academic institution between 2012 and 2019. Logistic regression analysis was used to measure association between the indication for tonsillectomy and the demographic variables gender, race/ethnicity, and age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…Despite such omitted data, in 2019 TE was the twelfth most common surgical procedure in the world (11,12). Certainly, upper airway obstruction and recurrent infections represent the leading indications to TE in children (13). What is less known about TE, however, is its relationship with cancer (14).…”
Section: Abstract Otorhinolaryngology Tradition Is That Tonsillectomy...mentioning
confidence: 99%
“…Despite such omitted data, in 2019 TE was the twelfth most common surgical procedure in the world (11,12). Certainly, upper airway obstruction and recurrent infections represent the leading indications to TE in children (13). What is less known about TE, however, is its relationship with cancer (14).…”
Section: Abstract Otorhinolaryngology Tradition Is That Tonsillectomy...mentioning
confidence: 99%
“…Additionally, the size of adenoids can be assessed using an endoscopic grading scale as per the study by Cassano et al [7]. Numerous studies have demonstrated a clear correlation between the preoperative size of tonsils and adenoids and obstructive symptoms [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%